SYSTEMATIC LITERATURE REVIEW: SISTEM ANTRIAN PADA PELAYANAN PUBLIK - Dwi Handoko Putra; Wilonotomo; Muhammad Fahrury Romdendine (Pendas : Jurnal Ilmiah Pendidikan Dasar, 2025)
Queue management systems are an essential and fundamental component in all service and product sectors. These systems are crucial because they are the main point of interaction between an organization and its clients. This study seeks to explore the theoretical foundations and methodological approaches applicable to the analysis of queuing systems. The study used a literature review methodology with PRISMA (Preferred Reporting Items for Systematic Reviews and Meta-analyses) guidelines, examining scientific papers from Google Scholar published between 2020 and 2025. The findings revealed that the Technology Acceptance Model (TAM) emerged as the dominant theoretical framework, while qualitative research methods, particularly survey-based approaches, were the most frequently used methodologies. In addition, SPSS software stood out as the primary analytical tool among researchers in this field.